Implant-bone-interface: Reviewing the impact of titanium surface modifications on osteogenic processes in vitro and in vivo - Stich, Theresia; Alagboso, Francisca; Křenek, Tomáš; Kovářík, Tomáš; Alt, Volker; Docheva, Denitsa (Bioengineering & translational medicine, 2022)
Titanium is commonly and successfully used in dental and orthopedic implants. However, patients still have to face the risk of implant failure due to various reasons, such as implant loosening or infection. The risk of implant loosening can be countered by optimizing the osteointegration capacity of implant materials. Implant surface modifications for structuring, roughening and biological activation in favor for osteogenic differentiation have been vastly studied. A key factor for a successful stable long-term integration is the initial cellular response to the implant material. Hence, cell-material interactions, which are dependent on the surface parameters, need to be considered in the implant design. Therefore, this review starts with an introduction to the basics of cell-material interactions as well as common surface modification techniques. Afterwards, recent research on the impact of osteogenic processes in vitro and vivo provoked by various surface modifications is reviewed and discussed, in order to give an update on currently applied and developing implant modification techniques for enhancing osteointegration.
Keywords: in vivo and in vitro; osteogenic differentiation; surface modifications; osteointegration; bone‐implant‐interface; titanium implants